DS OML decision support for the interpretation of oral mucosa lesions - Strassburg, Manfred; Quintessence Publishing Co. (Berlin : Quintessenz Verlag, 2007)
(Producer) Provides a decision-making tool for the diagnosis, differential diagnosis, and therapy of diseases of the oral mucosa. Encompasses over 800 clinical images and precise text information, primarily designed for the needs of the dental practice
Title from disc label
Authors, M. Strassburg, I.-V. Wagner, W. Schneider.
System requirements: Pentium with at least 300 MHz; 64 MB RAM (128 MB recommended); Windows 95, 98, ME, NT 4.0 (service pack 6), 2000, XP; graphics card; 1024x768 or 1280x960 pixel resolution at 24 bit color (True Color); CD-ROM drive with 8x read speed
Keywords: Mouth diseases -- Diagnosis; Mouth Diseases -- therapy; Decision Making, Computer-Assisted; Mouth Mucosa -- pathology